Biochemical complementation of chalcone synthase mutants defines a role for flavonols in functional pollen. - Mo, Y (1992)
Chalcone synthase catalyzes the initial step of that branch of the phenylpropanoid pathway that leads to flavonoids. A lack of chalcone synthase activity has a pleiotropic effect in maize and petunia mutants: pollen fertility as well as flavonoid synthesis is disrupted. Both maize and petunia mutants are self-sterile due to a failure to produce a functional pollen tube. The finding that the mutant pollen is partially functional on wild-type stigmas led to the isolation and identification of kaempferol as a pollen germination-inducing constituent in wild-type petunia stigma extracts. We show that adding micromolar quantities of kaempferol to the germination medium or to the stigma at pollination is sufficient to restore normal pollen germination and tube growth in vitro and full seed set in vivo. Further we show that the rescue ability resides in particular structural features of a single class of compounds, the flavonol aglycones. This finding identifies another constituent of plant reproduction and suggests that addition or removal of the flavonol signal during pollen germination and tube growth provides a feasible way to control plant fertility.